The influence of international cooperation between universities on the quality of education in the country - Gardocka, Teresa (НТУ "ХПІ", 2015)
The article analyzes the problems of European educational environment in the context of international cooperation between universities. There was an attempt to determine the place and role of Poland in the development of higher education in Ukraine and Lithuania. In the article there is considered the history of formation of Vilniaus Universitetas and Ivan Franko National University of Lviv with a focus attention on the participation of the international scientific community in their development. In addition, the article contains conclusions and generalizations about the impact of European international universities on the development of national higher education institutions and their role in establishing the quality standards of higher education.

У статті аналізуються проблеми Європейської освітньої середовищі в контексті міжнародного співробітництва між університетами. Була зроблена спроба визначити місце і роль Польщі у розвитку вищої освіти в Україні та Литві. У статті розглядається історія формування Вільнюського університету і Національного університету імені Івана Франка у Львові, з акцентом уваги на участь міжнародного наукового співтовариства в їх розвитку. Крім того, стаття містить висновки та узагальнення про вплив європейських міжнародних університетів на розвиток національних вищих навчальних закладів та їх роль у встановленні стандартів якості вищої освіти.
Dплив міжнародного співробітництва між вузами за якістю освіти в країні
Keywords: European universities; higher education; internationalization; globalization; educational activities; mobility of students; університети європейські; освіта вища; інтернаціоналізація; глобалізація; діяльність освітня; мобільність студентів